Polymer composition for improved grade plastics from recycled materials

By adding peroxide and polyolefin elastomer to the recycled polypropylene and using talc during the injection molding process, the problems of increased optical performance and insufficient mechanical properties of the recycled polymer composition during the injection molding process are solved, and the problem of increased optical performance and insufficient mechanical properties of the recycled polymer composition during the injection molding process is achieved. The excellent performance and low-tiger pattern effect of the high content recycled polyolefin composition are obtained.

CN119301190AActive Publication Date: 2025-01-10QCP HOLDING BV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380028272.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-23
Filing Date
2023-03-23
Publication Date
2025-01-10
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

The existing recycled polymer compositions have problems with increased optical properties during injection molding, resulting in tiger stripes and surface defects, and their mechanical properties and flow behavior are not excellent enough, making it difficult to prepare durable consumer products with high content of recycled polyolefins. .

Method used

60-80 wt% transfer recycled polypropylene (s-rPP) was used, combined with 0-0.03 wt% peroxide, 3-7 wt% heterophasic propylene ethylene copolymer and 10-30 wt% polyolefin elastomer ( POE), improves the melt flow rate of polypropylene through peroxide treatment, and adds talc during injection molding to optimize mechanical properties and flow behavior.

Benefits of technology

A unique balance of mechanical properties and flow behavior of high content recycled polyolefin compositions is achieved, significantly reducing tiger stripes, improving impact strength and molding behavior, and making the product performance close to or better than the use of original materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005046845240000081
    Figure BDA0005046845240000081
  • Figure BDA0005046845240000082
    Figure BDA0005046845240000082
  • Figure BDA0005046845240000091
    Figure BDA0005046845240000091
Patent Text Reader

Abstract

The present invention relates to a polymer composition comprising: (a) 60 to 80 wt% of recycled polypropylene (rPP); (b) 0 to 0.03 wt% of a peroxide; (c) 3 to 7 wt% of a heterophasic propylene ethylene copolymer; (d) 10 to 30 wt% of a polyolefin elastomer (POE); wherein components (a) to (d) are combined to 100%, and wherein the melt flow rate of component (a) has been increased by reaction with peroxide in the range of 60 to 80 g / 10 min, as determined according to ISO 1133 at 2.16 kg, 230 DEG C. The invention also relates to a method of forming a polymer composition in which the MFR of component (a) is increased by reaction with a peroxide in a first step and components (a)-(d) are added in a second step. The invention also relates to articles made from the novel polymer composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a new and improved polymer composition comprising a large amount of recycled polypropylene (PP) and polyethylene (PE). The present invention also relates to the use of such polymer composition in the manufacture of articles, articles manufactured from said polymer composition and a process for preparing such polymer composition. Background Art

[0002] The popularity of plastic packaging and the importance of environmental policies have led to an increase in the importance of recycled plastic materials.

[0003] The recycling of paper, textiles, glass or metals is already taking place on a large scale, either through separate collection or by sorting the recyclables. The recycling of plastic waste and the reuse of plastics are also increasing.

[0004] The replacement of virgin polymer compositions is considered the only way to solve the global plastic waste problem, stop the depletion of natural resources and promote a circular economy.

[0005] Hitherto, recycled polymer compositions are available in the form of flakes or granules obtained from the collection of commercially available polyolefin packages, containers or films, wherein polyolefin is present in the recycled polymer composition in a low percentage of 5-8 wt % and the remaining 92-95 wt % of the polyolefin is made of virgin polyolefin.

[0006] WO2020221756 describes compositions obtained from recycled polyolefins.

[0007] There remains a need for products made from recycled materials that have a good balance of mechanical and optical properties. For example, optical properties such as tiger stripes, flow-induced surface defects during injection molding are a problem when virgin materials are used, but are increasingly improved when recycled polyolefins are used.

[0008] The object of the present invention is to define a new polymer composition which can be used for the preparation of durable consumer goods based on 60 wt% or more of recycled polyolefins, having significantly reduced tiger stripes, excellent molding behavior and excellent impact strength. Summary of the invention

[0009] Accordingly, there is provided a polymer composition comprising:

[0010] (a) 60-80 wt% of transferred recycled polypropylene (s-rPP);

[0011] (b) 0-0.03 wt % of peroxide;

[0012] (c) 3-7 wt% of a heterophasic propylene ethylene copolymer;

[0013] (d) 10-30 wt% of polyolefin elastomer (POE);

[0014] wherein the amounts of components (a) to (d) are defined relative to the sum of (a) + (b) + (c) + (d) of the polymer composition, and wherein the melt flow rate of component (a) is in the range of 60 to 80 g / 10 min, determined according to ISO 1133 under 2.16 kg at 230°C.

[0015] The invention also provides a process for preparing the polymer composition, a polymer article prepared therefrom, and a process for preparing said article, in particular by injection molding.

[0016] An advantage of the polymer composition according to the invention is a unique balance of mechanical properties and flow behavior, resulting in a composition with a high content of recycled polyolefins having comparable or better properties than virgin material. DETAILED DESCRIPTION

[0017] The expression "comprising" means that components (a) to (d) must be present in defined amounts, and other components such as fillers, colorants and similar additives may be present in conventional amounts, e.g. up to 10 wt % based on the total amount of components (a) to (d). This means that the amount of components (a) + (b) + (c) + (d) preferably constitutes at least 90 wt % of the polymer composition.

[0018] Component (a): Diverted recycled polypropylene

[0019] Transferred recycled polypropylene (s-rPP) is obtained by processing recycled PP (rPP) with organic peroxides to higher melt flow rate and lower molecular weight.

[0020] rPP raw materials include plastic waste, mainly post-consumer waste (PCW) PP packaging waste, such as detergent and shampoo bottles, dairy cans and meat trays. rPP raw material waste can be pre-sorted by waste management companies. A suitable rPP source can be, for example, waste collected under DSD 324 (05-2012) and DSD 324-1 standards (03-2018).

[0021] The rPP DSD 324 (05-2012) raw material may include at least one of the following used, residue-discharging, rigid, system-compatible articles made of polypropylene, such as bottles, cups and trays, including secondary parts such as caps, labels, etc. The rPP DSD 324 (05-2012) raw material may include a maximum total amount of 6% by mass of impurities. Impurities in the rPP DSD 324 (05-2012) raw material may include <0.5% by mass of other metal articles, <1% by mass of rigid PE articles, <0.5% by mass of expanded plastics including EPS articles, <2% by mass of plastic films, and <3% by mass of other residues. Other examples of impurities in the rPP DSD 324 (05-2012) raw material may include glass, paper, board, paperboard, composite paper / paperboard materials (such as liquid packaging board), aluminized plastics, other materials (such as rubber, stone, wood, textiles, diapers) and compostable waste (such as food, garden waste).

[0022] The second standard for rPP is the PP DSD 324-1 standard (03-2018). This standard is very comparable to the above-mentioned PP DSD 324 standard, except that rPP can contain more film materials, up to about 10wt%. The film materials include rPP films (such as, for example, bi-oriented PP (BOPP)) PE films. The PP DSD 324-1 standard (03-2018) raw materials may include impurities with a maximum total amount of 4% by mass. Impurities in the PP DSD 324-1 standard (03-2018) raw materials may include <0.5% by mass of other metal items, <1% by mass of rigid PE items, <0.5% by mass of expanded plastics including EPS items, <1% by mass of paper, paperboard, cartons, composite paper / paperboard materials (such as liquid packaging paperboard), <3% by mass of other residues. Other examples of impurities in the PP DSD 324-1 standard (03-2018) feedstock may include glass, aluminized plastics, other materials (e.g. rubber, stone, wood, textiles, diapers) and compostable waste (e.g. food, garden waste).

[0023] The rPP may contain 25-75 parts by weight of packaging material (BOPP) and 75-25 pbw of a rubber-containing injection molding material out of 100 parts. This injection molding material may contain rubber, such as C2-C3 rubber, thermoplastic elastomer (TPE), ethylene propylene diene monomer rubber (EPDM) or ethylene propylene rubber (EPR).

[0024] Typically, when no rPP treatment is performed, the melt flow rate of rPP measured using ISO 1133-1:2011, 2.16 kg, T = 230°C ranges from 10 to 20. This MFR is too low to prepare a polymer composition with an appropriate balance of properties.

[0025] Therefore, the use of rPP obtained directly after cleaning the PP from the DSD 324, without further treatment, does not result in a polymer composition according to the present invention.

[0026] Preferably, the transferred recycled PP used in the present invention has a melt flow rate in the range of 60 to 80 g / 10 min measured using ISO 1133-1:2011, 2.16 kg, T=230° C. More preferably, component (a) has an MFR in the range of 65 to 75 g / 10 min.

[0027] It is important that the s-rPP has undergone MFR shift by reaction of rPP with peroxide before the other components of the composition are added. If the other components (heterophasic propylene ethylene copolymer and polyolefin elastomer (POE)) are present during the shift of rPP, a composition will be obtained that does not show a proper balance of properties.

[0028] The transfer of rPP is preferably carried out with an organic peroxide, more preferably with 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (CAS 78-63-7). The transfer is preferably carried out with 0.1-0.3 wt% of the organic peroxide. Alternatively, the organic peroxide may be present as a masterbatch, wherein the peroxide is dispersed in a polymer such as polypropylene (PP). For example, 10 wt% wt% organic peroxide is dispersed in 90 wt% PP to provide a 10 wt% masterbatch. To transfer rPP, a 10% masterbatch of 1-3 wt% peroxide may be used. Other masterbatches may also be used, and the skilled person may easily adjust the amount of masterbatch required to convert the rPP to the desired MFR.

[0029] The transfer typically occurs in an extruder at a temperature typically between 200°C and 270°C.

[0030] It was surprisingly found that varying the MFR before blending the other components and then combining the s-rPP with the heterophasic propylene ethylene copolymer and polyolefin elastomer (POE) results in a product with an improved balance of properties including tiger stripe reduction, high cold impact, high RT impact and high tensile strength.

[0031] Relative to the sum of (a) + (b) + (c) + (d) of the polymer composition, s-rPP is present in 60-80wt%, preferably 60-77.5wt%, more preferably 62-75wt%; the sum of (a) + (b) + (c) + (d) relative to the polymer composition can also be defined as the sum of (a) to (d) relative to the polymer composition.

[0032] Component (b), peroxide

[0033] Optionally, s-rPP, heterophasic propylene ethylene copolymer and polyolefin elastomer (POE) are blended together with a small amount of peroxide component (b). This component (b) is preferably present as a PP masterbatch, wherein the peroxide may be present in a weight ratio of peroxide to PP of 1:100-1:25, more preferably a weight ratio of peroxide to PP of 1:50-1:30. The amount of peroxide component b is between 0 and 0.03 wt% (based on wt% peroxide) relative to the sum of components a+b+c+d.

[0034] Component (b) should not be confused with the peroxide used to convert rPP into s-rPP prior to blending the different components to prepare the polymer composition according to the invention.

[0035] Component (b) can be used to fine-tune the flow properties of the polymer composition of the present invention.

[0036] Peroxides commonly used as crosslinking agents can be used. Preferably, organic peroxides are used. For example, the peroxide can be 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (DBPH). The latter is 101 is commercially available. Alternatives include 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, dicumyl peroxide, etc.

[0037] Component (c), heterophasic propylene ethylene copolymer

[0038] Suitable heterophasic propylene ethylene copolymers are described in US2020339794 and US2020263013, which are described herein by reference. Preferably it is a copolymer that satisfies the following conditions:

[0039] i) an ethylene-derived unit content ranging from 6.0 wt% to 16.0 wt%;

[0040] ii) a xylene-soluble fraction at 25° C. ranging from 15 wt % to 45 wt %;

[0041] iii) an intrinsic viscosity (η) of a xylene-soluble portion at 25° C. in the range of 4.0 to 9.0 dl / g; and

[0042] iv) Melt flow rate, measured according to ISO 1133 at 230°C with a load of 2.16 kg, ranges from 0.3 to 50.0 g / 10 min, more preferably from 0.5 to 5.0 g / 10 min.

[0043] Suitable examples include the preferred LyondellBasell Hifax X 1956A. Component (c) may be used in an amount of 3-7 wt%, preferably 4-6 wt%, relative to the sum of (a) to (d) of the polymer composition.

[0044] Component (d), polyolefin elastomer

[0045] Component (d) is an ethylene α-olefin copolymer (POE). An example of POE is C 2 -C 4 Copolymer, C 2 -C 6 Copolymer and C 2 -C 8 Copolymer. POE may preferably be C 2 -C 6 Copolymers or C having 70-80 wt%, more preferably 73-78 wt%, most preferably 74-77 wt% ethylene 2 -C 8 Copolymers; wherein wt % is relative to POE.

[0046] The POE used in the present invention preferably comprises ethylene (C 2 )Octene(C 8 ) metallocene rubber. The density of POE is preferably between 0.85-0.89, more preferably between 0.855-0.885, and most preferably between 0.86-0.875.

[0047] POE preferably has an MFR (190° C., 2.16 kg) of 0.3-1, more preferably 0.4-0.8, most preferably 0.45-0.7.

[0048] The POE is preferably selected from Infuse or Engage polymers, such as Infuse 9107, Infuse 9077 and Engage XLT 8677. Infuse 9077 available from DOW is preferred.

[0049] POE is present at 10-30 wt%, preferably 15-25 wt%, more preferably about 20 wt%, relative to the sum of (a) to (d) of the polymer composition.

[0050] Component e) Talc

[0051] The composition preferably contains talc. The talc may for example be unmodified and preferably has no surface coating or surface treatment. The talc may also be referred to as talc in this application. The talc may for example be an alpha nucleating agent, such as hydrated magnesium silicate or Steamic 00SDF.

[0052] Preferably, the talc is very finely ground talc. The inventors have found that the use of fine talc with a D50 of less than 4 microns, preferably less than 3 microns, even more preferably less than 2.5 microns in combination with recycled PP produces an increase in impact and tensile modulus and acts as a nucleating agent for the composition, thereby increasing the mechanical properties of the composition. D50 is measured by sedimentation diagram, sedimentation analysis, Stokes' law (ISO 13317-3).

[0053] Talc increases the stiffness and strength of the polymer composition and the articles produced. The talc content further affects the flow of the polymer composition during the molding process, especially for thin wall applications.

[0054] Talc is preferably present in the polymer composition at 1-10 wt%, preferably 2-5 wt% or 2.5-4 wt%. The best balance of properties can be achieved using a talc content of 2.5-3.5 wt% relative to the total composition. Amounts of talc below 1 wt% do not improve the properties of the composition, while amounts > 10 wt% give the composition a density that is too high for some applications and the amount of tiger stripes tends to increase above 10 wt%.

[0055] Additional components

[0056] The compositions may contain additional components including fillers, colorants, processing aids, as well as other polymers and recycle streams.

[0057] It is important to stay within the range defined above to obtain a polymer composition with excellent mechanical properties and aesthetic appearance that can be injection molded under typical conditions. In addition, it has been found that the order in which these components are mixed is relevant. In other words, component (a) must first undergo a transfer reaction with the peroxide before the further components are added.

[0058] The invention is illustrated by the following examples.

[0059] Example

[0060] A series of experiments have been carried out. Experiments 1-3 and 5-7 are comparative examples, in which s-rPP was used without pretreatment to convert it to the desired MFR and in which component c (Hifax) was not added.

[0061] The formulation is provided in Table 1 below.

[0062] Experiments C1-C3 showed performance with reasonable tiger stripes, but the modulus of the material was quite high, and the elongation at break and elongation at yield were too low, producing a very brittle material. The Charpy impact was 10 times lower than desired. The addition of Kraton rubber from C1 to C2 to C3 improved the Charpy slightly, but not enough.

[0063] In experiment C5, the amount of DOW infuse 9077 was increased relative to C1-C3, and rPE was added. As a result, the MFR was too low, the elongation at break and yield was too low, and the tiger stripe was very high.

[0064] Experiment C6 applies a different DOW Infuse 9177 in a higher amount compared to C1-C3. The performance is comparable to experiments C1-C3: Charpy impact and elongation values ​​are too low. This example shows a greater amount of tiger stripes.

[0065] Experiment C7 to C5 comparison: Now applied 10wt% Infuse 9177. Charpy impact is too low, elongation at break and elongation at yield are too low, and tiger stripe is very high.

[0066] It's hard to find the right balance of features.

[0067] Surprisingly, the best balance of properties was achieved in Experiment 4 (ad). E-modulus greater than 800 N / mm 2 The elastic behavior is sufficient. The impact strength at room temperature and low temperature is greatly improved.

[0068] Furthermore, Experiment 4 (ad) consistently provided molded products without visible tiger stripes or other surface defects.

[0069] The results are provided in Table 2 below.

[0070]

[0071] Table 1

[0072] sample C1 C2 C3 4a 4b 4c 4d C5 C6 C7 QCP PP300U (MFR 70) grey or ivory % 71,0 71,0 71,0 71,0 QCP PP300t (MFR 50) grey or ivory % 89,8 87,8 85,8 69,8 89,8 69,8 LyondellBasell Hifax X 1956A % 5,0 5,0 5,0 5,0 DOW Infuse 9077 % 5,00 5,00 5,00 20,00 20,00 20,00 20,00 10,00 DOW Infuse 9177 10,00 10,00 QCP PE5603 grey or ivory % 17,00 20,00 Kraton G1657MS % 2,0 4,0 2,0 Steamic OOSd(Talc) % 5,00 5,00 5,00 3,00 3,00 3,00 3,00 Masterbatch Irganox B225 30% % 0,20 0,20 0,20 0,50 0,50 0,50 0,50 0,75 0,20 0,20 Exxelor PE1040 % 0,50 DBPH 10% on PP % 0,50 0,50 0,50 0,50

[0073] Table 2

[0074]

[0075] Table 2, continued

[0076]

[0077] Charpy is performed according to NEN-ISO 179 / eA, moulded strips 527 / 1A.

Claims

1. A polymer composition comprising: (a) 60-80 wt% of transferred recycled polypropylene (s-rPP); (b) 0-0.03 wt % of peroxide; (c) 3-7 wt% of a heterophasic propylene ethylene copolymer; (d) 10-30 wt% of polyolefin elastomer (POE); wherein the amounts of components (a) to (d) are defined relative to the sum of (a) to (d) of the polymer composition, and wherein component (a) has a melt flow rate (MFR) of 60 to 80 g / 10 min, measured according to ISO 1133 at 2.16 kg, 230°C.

2. The polymer composition according to claim 1, wherein the composition further comprises (e) 1 to 5 wt% of fine talc.

3. The polymer composition according to claim 1 or 2, wherein component (a) has an MFR of 65 to 75 g / 10 min, measured according to ISO 1133 at 2.16 kg and 230°C.

4. The polymer composition according to any one of claims 1 to 3, wherein the s-rPP is obtained by transferring recycled PP with an organic peroxide, wherein the recycled PP is obtained from PP plastic waste collected under DSD 324 (05-2012) and DSD 324-1 standards.

5. The polymer composition according to any one of claims 1 to 4, wherein the MFR of component (a) has been increased by reaction with recycled PP and an organic peroxide before blending components (a) to (d).

6. The polymer composition according to any one of the preceding claims, wherein component (a) is preferably present in 60-77.5 wt%, more preferably 62-75 wt%, relative to the sum of (a) to (d) of the polymer composition.

7. A polymer composition according to any one of the preceding claims, wherein component (b) is an organic peroxide, preferably 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (DBPH).

8. A polymer composition according to any one of the preceding claims, wherein the sum of the amounts of components (a) + (b) + (c) + (d) is at least 90 wt% of the polymer composition.

9. A polymer composition according to any one of the preceding claims, wherein component (c) satisfies the following conditions: i) an ethylene-derived unit content ranging from 6.0 wt% to 16.0 wt%; ii) a xylene-soluble fraction at 25° C. ranging from 15 wt % to 45 wt %; iii) an intrinsic viscosity (η) of a xylene-soluble portion at 25° C. in the range of 4.0 to 9.0 dl / g; and iv) Melt flow rate, measured according to ISO 1133 at 230°C with a load of 2.16 kg, ranges from 0.3 to 50.0 g / 10 min, more preferably from 0.5 to 5.0 g / 10 min.

10. The polymer composition according to any one of claims 1 to 9, wherein component (c) is used in an amount of 4 to 6 wt% relative to the sum of (a) to (d) of the polymer composition.

11. A polymer composition according to any of the preceding claims, wherein component (d) is selected from C2-C4 copolymers, C2-C6 copolymers and C2-C8 copolymers, preferably C2-C6 copolymers or C2-C8 copolymers with 70-80 wt% ethylene, more preferably 73-78 wt% ethylene, most preferably 74-77 wt% ethylene; wherein wt% is relative to the POE.

12. A polymer composition according to any one of the preceding claims, wherein component (d) is present in 15-25 wt%, more preferably about 20 wt%, wherein wt% is relative to the sum of (a) to (d) of the polymer composition.

13. A method for preparing a polymer composition according to any one of claims 1 to 11, wherein in a first step, the MFR of component (a) is increased to within the range of 60 to 80 g / 10 min by reacting recycled PP obtained from PP plastic waste collected under DSD 324 (05-2012) and DSD 324-1 standards with peroxide, as measured at 230° C. under 2.16 kg according to ISO 1133, and in a second step, components (a) to (d) are added and blended.

14. An article made from the composition according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Compositions obtained from recycled polyolefins

    US20200263013A1

  • Compositions obtained from recycled polyolefins

    US20200339794A1

  • Polymer composition for improved grade plastics from recycled material

    WO2020221756A1

  • Method for making heterophasic polymer compositions

    US20180237625A1

  • Pp-rich material composition having high stiffness and processability

    US20200385555A1